A Review on Influencing Welding Parameters of Super Alloys. Issue 1 (November 2020) - Raja, S; Saranya, R; SaiYaswanth, V; SachinAdithya, A; Rohith Kumar, M B
Abstract: Manufacturing industries play a vibrant role in economic development and significant growth of a country. Among all different industries, sheet metal industry is irreplaceable in our routine life. Sheet metal applications include in automobiles, aircrafts, computer panels, building roofs etc. Various manufacturing process of sheet metal industry consists of shearing, bending, welding and deep drawing. Welding is one of the vital process in engineering business. Welding is the best operative method of joining similar and dissimilar components together. Choice of influencing process parameters is very much critical in welding for the purpose of obtaining good quality weldments with preferred mechanical properties and enhanced serviceability. This is impossible with single welding method that yields the optimum weld in all conditions. The choice of welding process depends upon the service environment, time, cost, and deposition rate. Superalloy is an alloy having greater mechanical strength and high corrosion resistance in high temperature applications. Superalloys are of, Nickel, Cobalt and Iron built possessing the crystal structure of Face Centered Cubic (FCC) austenitic. Typical examples of super alloys include Inconel, Hastelloy, Waspaloy, Rene alloys, Incoloy. Among these, Hastelloy is a nickel based superalloy containing the major proportion as Nickel 57%, Chromium 15.5% and Molybdenum 16% with the remaining in smaller proportions. Hastelloys are employed by the chemical industries for their Corrosion-Resistant property. The characteristics of Hastelloy include high resistance to localized corrosion in welding and fabrication. Hastelloy are of different grades optimised for specific purpose. Hastelloy alloys of "C-type" alloys are the most versatile. Hastelloy C276 alloy is a nickel alloy engaged in petro chemical and related industries possessing corrosive chemicals. Hastelloy C276 is ductile in nature, suitable for welding, forming and has high resistance to corrosion. Hastelloy C276 alloy is welded by the fusion welding process. The low quantity of carbon existence prevents carbide precipitation to keep resistance to inter granular attack in thermally affected zones. Every industry requires to attain a good quality of weld with great productivity and low processing cost with commanding weld joint.